RateSkiII: mining data from log file to classify children’s ICT skill / Mohd Talmizie Amron … [et al.] - Amron, Mohd Talmizie; Mohamad, Norizan; Dahlan, Azlin; Rizman, Zairi Ismael (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
In Terengganu, the Year 6 school children have been given e-books to help them keeping pace with the technology. Thus, the ability to assess these children's competency skill in ICT is very important to determine their progress in becoming fully computer competent. Learning the children's behavior and interaction towards the use of computer enable us to identify the incompetent ones for necessary 'skill upgrade' training. However, learning user behavior can be very time-consuming since the evaluator needs to be present and observe the direct actions performed by each user on a given task. In this situation, the presence of observers may hinder these children from demonstrating their actual skills. We present RateSkill that analyzes and interprets the children's activities in completing a set of given tasks. Their activities are captured and stored into log files which are then read by RateSkill application. The log file analysis allows the characterization of the children's behavior that relates to their actual competency skills. RateSkill is equipped with its ability to classifiy the children's skill into beginner, intermediate or expert level. The RateSkill has great potential to be commercial led to suit the demands of other domains such as future employers seeking for ICT competent candidates as well as current employers looking for ways to reduce the 'skills gap' among the employees.